2021
DOI: 10.3390/jcm10112399
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Instability Is Common in HIV-Exposed Uninfected Newborns

Abstract: Worldwide, one million HIV-exposed uninfected (HEU) children are born yearly, and chronic health impairments have been reported in these children. Mitochondrial DNA (mtDNA) instability and altered mtDNA content have been evidenced in these children, but an exhaustive characterization of altered mitochondrial genomes has never been reported. We applied deep mtDNA sequencing coupled to the deletion identification algorithm eKLIPse to the blood of HEU neonates (n = 32), which was compared with healthy controls (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Out of the 24 samples collected at D7, 22 had been previously analyzed with eKLIPse version-1 algorithm [ 28 ], and analyses were repeated with the new version of the software. The percentage of children with mtDNA alterations was similar regardless the version of eKLIPse.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the 24 samples collected at D7, 22 had been previously analyzed with eKLIPse version-1 algorithm [ 28 ], and analyses were repeated with the new version of the software. The percentage of children with mtDNA alterations was similar regardless the version of eKLIPse.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we did not have the opportunity to test HUU to compare our observations to an HIV-unexposed control group. However, we previously analyzed DBS collected during the same period from healthy French newborns and found no mtDNA deletion [ 28 ]. We have previously showed that neither the use of DBS nor the duration of storage introduced artefactual deletions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations